The influence of seed size on emergence of seedlings and plant development in grain crops with special reference to seeding depth - Rolf Manner (Agricultural and Food Science, 1963)
The influence of seed size on emergence of seedlings and plant development was studied in a number of trials with special reference to seeding depth. The results of the study lead to the following conclusions: The number of emerging seedlings and the number of developing shoots per 100 sown germinative seeds were smaller with small seeds than with large seeds. The influence of seeding depth on the percentage of emerging seedlings was more marked with small seeds than with large seeds. Differences were found between different crops. The strongest dependence of the observed quantities on seed size was displayed by winter rye at a great seeding depth. The differences between the studied crops could not be explained on the basis of differences in 1000-seed weights.